(Woman/Fire) in Poetry: O This Female by Othman Lousif – A Model - lazargi, toufik (El Omda in Linguistics and Discourse Analysis, 2018)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:a6b2ebb2-304a-48ab-8736-5ad337282e90-48" data-testid="conversation-turn-98" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="d9476f5f-3974-40f2-83e5-18748c34557e" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> The concept of fire among us Muslims is closely linked to doctrinal beliefs and, correspondingly, to Paradise. Fire is also intimately connected with human life, ever since it was discovered thousands of years before the Common Era. The notion of fire has likewise been associated with the nature of human emotions; in much of the poetry and prose I have studied, longing has often been metaphorically linked to fire. Additionally, my own circle of inquiry expanded after reading O This Female by the Algerian poet Othman Lousif, particularly regarding the relational ties between certain expressions. A central question arose: why is the beloved woman described as fire or through its derivatives? This question drove my inquiry as I repeatedly reread this collection, noticing that hardly any poem in his oeuvre lacks a poetic intertwining of (Woman/Fire).